Tomato Rootstocks Mediate Plant-Water Relations and Leaf Nutrient Profiles of a Common Scion Under Suboptimal Soil Temperatures - Bristow, Steven T.; Hernandez-Espinoza, Leonardo H.; Bonarota, Maria-Sole; Barrios-Masias, Felipe H. (Frontiers in Plant Science, 2021)
Environments with short growing seasons and variable climates can have soil temperatures that are suboptimal for chilling sensitive crops. These conditions can adversely affect root growth and physiological performance thus impairing water and nutrient uptake. Four greenhouse trials and a field study were conducted to investigate if rootstocks can enhance tomato performance under suboptimal soil temperatures. In a controlled greenhouse environment, we exposed four commercial rootstocks (Estamino, Maxifort, RST-04-106T, and Supernatural) grafted with a common scion (cv. BHN-589) and the non-grafted cultivar (BHN-589) to optimal (mean: 24 °C) and suboptimal soil temperatures (mean: 13.5 °C). Several root and shoot physiological traits were evaluated: root hydraulic conductivity and conductance, root anatomy, leaf gas exchange, leaf δ13C, shoot C and N, and biomass. Under field conditions, the same five phenotypes were evaluated for canopy growth, NDVI, leaf nutrients, biomass, and yield. Suboptimal soil temperatures (SST) decreased root hydraulic conductivity (Lp), conductance (KR), stomatal conductance (gs), and plant biomass. Under SST, hydrostatic Lp decreased more than osmotic Lp (Lp*hyd: 39-65%; Lp*os: 14-40%). Some of the reduced conductivity was explained by the increased cortex area of primary roots observed under SST (67-140%). Under optimal soil temperatures, all rootstocks conferred higher gs than the non-grafted cultivar, but only two rootstocks maintained higher gs under SST. All phenotypes showed greater reductions in shoot biomass than root biomass resulting in greater (~20%) root-to-shoot ratios. In the field, most grafted phenotypes increased early canopy cover, NDVI, shoot biomass, and fruit yield. Greenhouse results showed that Lp*os may be less affected by SST than Lp*hyd and that reductions in Lp may be offset by enhanced root-to-shoot ratios. We show that some commercial rootstocks possess traits that maintained better rates of stomatal conductance and shoot nitrogen content, which can contribute towards better plant establishment and improved performance under SST.